KANDUNGAN ANTOSIANIN DAN ANTOSIANIDIN DARI JANTUNG PISANG KLUTUK (Musa brachycarpa Back ) DAN PISANG AMBON (Musa acuminata Colla) [Anthocyanin Content and Identification of Anthocyanidin of Banana Bract Klutuk variety (Musa brachycarpa Back) and Ambo - Lydia Ninan Lestario; Dhanu Lukito; Kris Herawan Timotius (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2009)
The aims of this research were to determine total anthocyanin content and to explore the type of anthocyanidin of banana bract klutuk variety and ambon variety. The total anthocyanin content was determined with pH differential method, the data were then statistically-analyzed with t-test with 5 replications, whereas the exploration of anthocyanidin was based on Rf value and maximum absorbance of the spots on TLC, and also time retention of the peak on HPLC equiped with anthocyanidin standards. The results showed that the total anthocyanin content of banana bract of klutuk variety 909,44 ± 280,53 mg/ 100 g; which was significantly different from ambon variety 1515,40 ± 193,74 mg/ 100 g. The type anthocyanidin of banana bract of klutuk variety include delphinidin and cyanidin, whereas ambon variety were delphinidin, cyanidin, and pelargonidin.